1994
DOI: 10.1042/bj3040027
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements of apo-a for the lipoprotein-a assembly

Abstract: Lipoprotein-a [Lp(a)], one of the most atherogenic lipoproteins, is composed of a low-density lipoprotein (LDL) core in addition to an apo-a of variable size which is linked to apoB by a disulphide bridge. Lp(a) synthesized in vitro by incubation of recombinant apo-a (r-apo-a) with LDL is physico-chemically indistinguishable from native Lp(a). The synthesis of Lp(a) in vitro proceeds in two steps. In the first step, one of the unique kringle-IVs (K-IVs) in apo-a binds to a Lys residue of apoB; in the second st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…2 As such, the closed conformation of apo(a) is disrupted when truncated apo(a) variants are used. This is important in that the studies used to identify domains in apo(a) that are required for Lp(a) assembly have been conducted using truncated apo(a) variants (11,14,20,21). In light of our recent discovery of the role of the conformational status of apo(a), a quantitative re-evaluation of the role of the respective WLBS is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As such, the closed conformation of apo(a) is disrupted when truncated apo(a) variants are used. This is important in that the studies used to identify domains in apo(a) that are required for Lp(a) assembly have been conducted using truncated apo(a) variants (11,14,20,21). In light of our recent discovery of the role of the conformational status of apo(a), a quantitative re-evaluation of the role of the respective WLBS is required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed by several investigators have underscored the importance of KIV 6 (10,14,20,21) and possibly KIV 7 (10,14,21) in this process. Previous data from our group also suggest that the WLBS in apo(a) KIV 8 plays a major role in non-covalent binding to LDL (14); all studies to date have demonstrated no role for apo(a) KIV 5 .…”
mentioning
confidence: 99%
“…Studies using truncated derivatives of apo(a) have suggested a role for KIV types 6 and 7 in Lp(a) formation (22,23); studies by Trieu and McConathy (7) have shown a role for apo(a) KIV type 6 and possibly type 7 in the initial noncovalent association of apo(a) and apoB-100. Our own studies using truncated r-apo(a) variants have shown a role for KIV types 6 -8 in noncovalent binding to apoB-100 (8).…”
Section: Figmentioning
confidence: 99%
“…Samples (50 l aliquots) were fractionated by SDS-PAGE (3.75-12.5%) for 1 h at 150 V, transferred to nitrocellulose followed with the visualization by an enhanced chemiluminescence assay (ECL; Amersham Pharmacia Biotech, Little Chalfont, UK) after incubation with specific antibodies as described previously. 29,34 Gene Therapy…”
Section: Rna Analysismentioning
confidence: 99%